The Effect of Observing Animated Model and Static Images and Combined Model on Motor Learning of Handstand Balance Skill - Akbar Ghavami; Fatemeh Hosseini; Hasan Mohammadzadeh; Behnam Maleki; Hossien Borhani (University of Tehran, 2012)
The aim of this research was to investigate the effect of observing animated model, static images and combined model on motor learning of handstand balance skill. 45 subjects (mean age 8.03±1.7 yr) were randomly divided into three experimental groups: observation of animated model, static images, combined model. Subjects trained handstand balance skill for three weeks (three sessions per week). Pretest, acquisition test and retention test was performed for three groups. Subjects' scores were obtained by calculating mean scores of three gymnastic referees based on specific norm of Gymnastics Federation. The results of two-way ANOVA with repeated measures showed significant effects of the three methods on motor learning of handstand balance skill (pv=0.001). Also, the results showed no significant difference between the combined model and animation model groups (pv=0.156). Finally, both combined model and animation model groups were better than static images group (pv=0.001). As a whole, results suggest that observation of animation is a useful modeling method of learning handstand balance skill in childhood. It is also suggested that static images be used along with the animations as a supplement.